Reviewing the role of ecosystems services in the sustainability of the urban environment: A multi-country analysis - Filho, W.L. (Elsevier Ltd, 2020)
The urban environment is characterised by many pressures caused by population growth, transport (and its related emissions), and the damage to green areas. Yet, there is a variety of ecosystem services available in urban areas, which may be deployed to ameliorate the current problems and foster their sustainability. This paper reviews the role of ecosystem services as tools for sustainability, based on an urban setting. It also describes a series of multi-country case studies, where an assessment of their functions using a set of benefits valuation approaches such as health benefits, economic benefits, social benefits and benefits to climate resilience, are provided, along with an appraisal of their role in up-keeping the overall quality of the urban environment in the studied areas. Policy recommendations aimed at enhancing the role of ecosystem services, and fostering sustainability in the sampled sites -and beyond-are provided. Â© 2020 Elsevier Ltd